2014
DOI: 10.1016/j.steroids.2014.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Diallyl sulfide inhibits diethylstilbestrol induced DNA damage in human breast epithelial cells (MCF-10A)

Abstract: Breast cancer is the second leading cause of cancer deaths in women in the United States. Diethylstilbestrol (DES) is a synthetic estrogen that has been shown to cause cancer in animals and humans, altering cell viability as well as inducing DNA damage. Diallyl sulfide (DAS) is a garlic organosulfide that has been shown to inhibit both the initiation and promotion phases of cancer in vivo and in vitro, as well as reduce the risk of cancer in epidemiological studies. MCF-10A cells, regarded as a normal breast e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…By stimulating the nucleotide repair machinery modulated by these genes [4446], DAS was postulated to reduce the occurrence of DNA adduct formation (anti-carcinogenic). In later studies, protective effects of DAS against chemical induced-DNA damage were confirmed in human breast epithelial cells [47, 48]. …”
Section: Protective Effects Of Dasmentioning
confidence: 99%
“…By stimulating the nucleotide repair machinery modulated by these genes [4446], DAS was postulated to reduce the occurrence of DNA adduct formation (anti-carcinogenic). In later studies, protective effects of DAS against chemical induced-DNA damage were confirmed in human breast epithelial cells [47, 48]. …”
Section: Protective Effects Of Dasmentioning
confidence: 99%
“…Diallyl disulfide up-regulated expression of miR-34a in MDA-MB-231 cells, so it possessed cytotoxicity effects [ 143 ]. Moreover, diallyl sulfide inhibited diethylstilbestrol-induced DNA damage in human breast epithelial cells (MCF-10A), and reduced lipid peroxidation [ 144 ]. Besides, after treatment with S -allyl mercaptocysteine, cell growth was inhibited in human breast cancer cell lines MCF-7 (ER + ) and MDA-MB-231 (ER − ) via inducing cell cycle arrested in G 0 /G 1 phase.…”
Section: Garlicmentioning
confidence: 99%
“…New research about phytonutrients and organosulfides in particular and how they affect our health are rapidly becoming a part of medical science. [53][54][55][56][57] A c c e p t e d M a n u s c r i p t…”
Section: Resultsmentioning
confidence: 99%